Integrated Chinese Level 1 Part 1 : Workbook. Simplified Characters - Liu Yuehua, ....-; Yao Tao-chung, ....- (Boston : Cheng & Tsui, 1997)
This new edition of Integrated Chinese is an outstanding achievement. Complete with interesting cultural notes, useful authentic materials, and a wealth of interactive exercises, the authors have outdone themselves AGAIN!
Keywords: Chinees; taal